Paleomagnetic Constraints From South Georgia on the Tectonic Reconstruction of the Early Cretaceous Rocas Verdes Marginal Basin System of Southernmost South America. Issue 2 (18th February 2022) - Beaver, Douglas G.; Kent, Dennis V.; Dalziel, Ian W. D.
Abstract: South Georgia exists as a microcontinent along the North Scotia Ridge ∼1, 700 km east of Cape Horn. The tectonostratigraphic units of South Georgia have long been correlated with those of the Fuegian Andes of southernmost South America. Accordingly, South Georgia has been regarded as a continuation of the Late Jurassic–Early Cretaceous Rocas Verdes marginal basin system, formerly situated south of Burdwood Bank and east of Cape Horn. To test this, paleomagnetic analysis of samples from the Larsen Harbour Complex, Drygalski Fjord Complex, and Annenkov Island Formation of South Georgia showed that 21 sites yield a mean direction of D = 328.5°, I = −62.1° (a95 = 3.5°) and a paleomagnetic pole at 068.2°E, 67.2°N, A95 = 4.7°. The consistency of directions and strong polarity bias, plus indications of a negative differential tilt test, point to a secondary magnetization acquired in the Late Cretaceous. Comparison of predicted versus observed directions for South Georgia relative to stable South America indicate 27.2 ± 11.2° of counter‐clockwise rotation (and 10.5° ± 4.5° of northward tilting) since the acquisition of magnetization. These results are consistent with paleomagnetic studies from the Fuegian Andes and support a paleoposition of the South Georgia microcontinent south of Burdwood Bank as strongly indicated by the geologic evidence. Partitioning this rotation between oroclinal bending during the Rocas Verdes basin collapse in the Late Cretaceous and left‐lateral translation along the North Scotia Ridge is not possible on paleomagnetic grounds, but the co‐linearity of Andean structures between the restored microcontinent and Tierra del Fuego indicates the former. Plain Language Summary: The South Atlantic island of South Georgia forms the mountainous, glaciated, core of a microcontinent. Located some 1, 700 km east of Cape Horn at the southern tip of South America, it is one of the most isolated fragments of continental crust on Earth. For many decades geological evidence has been accumulating that points to the island and hence the entire microcontinent being a displaced fragment of the Andean Cordillera of Tierra del Fuego. To test this hypothesis we collected oriented samples from igneous rocks on the main and offshore islands. The results are directly comparable to those obtained from samples from Tierra del Fuego and therefore support the geological evidence that the microcontinent originated as a continuation of the Andean Cordillera and was displaced eastward relative to South America during the opening of the South Atlantic Ocean basin. Key Points: South Georgia is a microcontinent on the Scotia Ridge regarded as a continuation of the Andes. To test this, oriented samples were collected The paleomagnetic results agree with studies from the Andes supporting the paleoposition of the South Georgia indicated by the geology Partitioning this rotation between oroclinal bending and translation along the North Scotia Ridge is not possible on paleomagnetic grounds